Rapid and accurate detection of carbapenemase genes inEnterobacteriaceaewith the Cepheid Xpert Carba‐R assay. Issue 9 (September 2016) - Smith, Marion; Diederen, Bram; Scharringa, Jelle; Leversteijn‐van Hall, Maurine; Fluit, Ad C.; Cohen Stuart, James
Abstract : N/A: Rapid and accurate detection of carbapenemase‐producing Enterobacteriaceae is pivotal for adequate antibiotic therapy and infection control. The Cepheid Xpert Carba‐R assay detects and identifies the most prevalent carbapenemases (KPC, VIM, IMP, NDM and OXA‐48), using automated real‐time PCR. The test performance of the Xpert Carba‐R was evaluated with 129 well‐characterized non‐repeat Enterobacteriaceae isolates, suspected for carbapenemase production, i.e. with meropenem MICs >0.25 mg l ‐1 . The isolate collection contained 100 carbapenemase‐producing isolates (36 KPC‐2 or KPC‐3, 20 VIM‐1, 4 KPC‐2 plus VIM‐1, 5 NDM‐1, 2 IMP‐1, 1 IMP‐28, 1 IMP‐1 plus VIM‐1 and 31 OXA‐48 like) and 29 negative control isolates producing extended‐spectrum β ‐lactamase and/or AmpC β ‐lactamases. PCR and sequencing of β ‐lactamase genes were used as reference tests. The sensitivity of the Xpert Carba‐R was 100 % (100/100), with a 100 % (29/29) specificity. The time to result was approximately 55 min with a hands‐on time of only 1 min per isolate. In conclusion, the Carba‐R assay is a rapid and accurate instrument for the confirmation and identification of the bla KPC, bla VIM, bla IMP, bla NDM and bla OXA‐48 genes.